Digitalization of prevention and treatment and the combination of western and Chinese medicine in management of acute heart failure - Wang, Yingxin; Cui, Herong; Li, Liwen; Cao, Yajing; Qu, Hanyun; Ailina, Halisi; Dou, Zhili; Tang, Chuwei; Qin, Wanli; Wang, Chenlu; Yang, Xue; Feng, Shixing; et al. (Frontiers in Cardiovascular Medicine, 2023)
Digitalization has emerged as a new trend in healthcare, with great potential and creating many unique opportunities, as well as many challenges. Cardiovascular disease is one of the major causes of morbidity and mortality of disease worldwide, and the threat to life of acute heart failure is evident. In addition to traditional collegiate therapies, this article reviews the current status and subdisciplinary impact of digital health care at the level of combined Western and Chinese medicine therapies and further discusses the prospects for its development, with the aim of playing an active role in the combination of digital and Western and Chinese medicine in the management of acute heart failure to support the the development of cardiovascular health in the population.